Cavite : el viejo : kasaysayan, lipunan, kultura - Calairo, Emmanuel Franco. 4 0 16; 5 ([Dasmariñas] : Cavite Historical Society, 1998)
History of Cavite, one of the provinces in the Philippines.
Hunyo 1998.;We observe the centennial of our hard-won independence--Front flap of cover.;Errata slip tipped in at end.
Includes bibliographical references (p. [165]-176) and index.
In Tagalog.
Keywords: 2 -- 0; 6; 20; History. -- Cavite Province (Philippines) -- 20; 2